PERAN LEMBAGA BANTUAN HUKUM DALAM PENDAMPINGAN HUKUM MASYARAKAT MISKIN PERSPEKTIF HUKUM ISLAM - Muhammad, Fadhel; A. Qadir Gassing; Nurfaika Ishak (Universitas Islam Negeri Alauddin Makassar, 2023)
Main research problem how the role of LBH Advocacy Cares for Nation legal assistance to poor from perspective of Islamic law. This research is classified as qualitative with the research approach used is the syar'i approach and legislation. Sources of data this study became informants were Achyar and Najir. Data collection method used observation. Research instruments used obtain the data are laptops, cellphones, interview. Data processing technique is inductive, Analysis based on specific data. Results of research on legal status accordance with Law No. 16 of 2011 are improvements to previous regulations regarding Legal Aid. If they dont carry out their obligations, there subject to sanctions in Article 7 of Law No. 18 of 2003. As well providing legal assistance according the view Islamic law, Islam is religion that upholds justice. Implication this research is that government, society must pay attention to and support LBH its role in providing legal guidance to community that brings good things wider community.